2011
DOI: 10.1089/end.2011.0217
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Fidelity of the R.E.N.A.L. Nephrometry Score

Abstract: The R.E.N.A.L. NS system is a comprehensive and reproducible tool that may aid surgeons in communicating tumor characteristics effectively. Interobserver correlation is high, rendering it a high fidelity assessment tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
4
26
1
Order By: Relevance
“…In our cohort of patients the mathematical model C-Index, which is a measure of tumor centrality, showed the highest level of agreement amongst readers and appeared to be the least prone to subjectivity of the three systems. Consistent with this finding and those of prior studies [9,14,15], the analysis of the IOV of each system's individual components showed that the (R)adius and the (A)nterior/posterior subscales of the R.E.N.A.L. system and tumor size in the PADUA system had the highest concordance rates amongst readers while the (L)ocation relative to polar lines (R.E.N.A.L.)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort of patients the mathematical model C-Index, which is a measure of tumor centrality, showed the highest level of agreement amongst readers and appeared to be the least prone to subjectivity of the three systems. Consistent with this finding and those of prior studies [9,14,15], the analysis of the IOV of each system's individual components showed that the (R)adius and the (A)nterior/posterior subscales of the R.E.N.A.L. system and tumor size in the PADUA system had the highest concordance rates amongst readers while the (L)ocation relative to polar lines (R.E.N.A.L.)…”
Section: Discussionsupporting
confidence: 93%
“…Good concordance and kappa values amongst readers were also found in studies on IOV of the R.EN.A.L. system used for open or laparoscopic PN patients, respectively [14,15]. In these studies, however, scores were assigned by small groups of urologists at different stages of professional development but with similar urological training.…”
Section: Discussionmentioning
confidence: 96%
“…nephrometry has been shown to be user-friendly and reproducible with a high degree of interobserver reliability. 12,20 Limitations of the scoring system were highlighted by Kutikov and Uzzo, including the impossibility of reaching the maximum score of 12 and the fact that the difference between each unit of scoring does not represent equal quanta of surgical complexity. 8 One item that can be improved is the incorporation of hilar tumors into the scoring system as opposed to simply using it as a suffix.…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver correlation is high, rendering it a high fidelity assessment tool. 12 Similar to Canter et al, other groups have shown that RENAL NS predicted surgeon preference for selection of RN versus PN in retrospective analyses. 13 Other standardized scoring systems include the preoperative aspects and dimensions used for anatomic (PADUA) classification and centrality (c)-index scores.…”
mentioning
confidence: 61%
“…Median operating time was 270 minutes, and median blood loss was 150 mL. Median WIT was 20 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) minutes and median hospital stay was 3 days. One patient developed postoperative hemorrhage and pulmonary embolism.…”
Section: Less/notes Pnmentioning
confidence: 99%